2008
DOI: 10.1186/1753-2000-2-17
|View full text |Cite
|
Sign up to set email alerts
|

Frequency, stability and differentiation of self-reported school fear and truancy in a community sample

Abstract: Background: Surprisingly little is known about the frequency, stability, and correlates of school fear and truancy based on self-reported data of adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 29 publications
2
18
0
3
Order By: Relevance
“…This term provides no suggestions of causality but, rather can be understood by the functions that are served by nonattendance. While attractive to many, others prefer to maintain a classificatory distinction between school refusal and truancy (Havik, Bru, & Ertesvåg, ; Steinhausen, Müller, & Winkler, ).…”
Section: Conceptualisationmentioning
confidence: 99%
See 1 more Smart Citation
“…This term provides no suggestions of causality but, rather can be understood by the functions that are served by nonattendance. While attractive to many, others prefer to maintain a classificatory distinction between school refusal and truancy (Havik, Bru, & Ertesvåg, ; Steinhausen, Müller, & Winkler, ).…”
Section: Conceptualisationmentioning
confidence: 99%
“…Steinhausen et al. () obtained self‐reports from 834 Swiss children aged between six and seventeen at two‐time points. The researchers found that, at the first‐time point (student mean age = 13 years), 104 children reported some form of school absenteeism.…”
Section: Conceptualisationmentioning
confidence: 99%
“…As mentioned, the psychological literature on school absenteeism generally emphasizes school refusers, not truants, suffer from mental health difficulties, since school refusers are thought to be motivated to absenteeism due to mental health issues. But research has found that truant youth also suffer from mental health problems (e.g., Hodges & Kim, 2000; Steinhausen et al, 2008), though the magnitude and nature of emotional problems among truant youths may differ from those among school refusers. Importantly, the data in this study do not indicate that the youths’ school absenteeism was directly related to their mental health problems, only that the youths were truant and possessed mental health problems.…”
Section: Discussionmentioning
confidence: 99%
“…In a second study of mental health problems and truancy, Steinhausen, Muller, and Metzke (2008) compared levels of mental health problems among school refusers (youths who indicated they were afraid of attending school), truant youths (youths who indicated that they skipped/cut classes), and control youths (those not identified as school refusers or truants). Steinhausen et al used the Youth Self Report (YSR), which is a version of the CBCL for self-reporting among older children and adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Existe una cantidad ingente de investigaciones que han tratado de identificar, catalogar y definir los miedos de niños y adolescentes en términos generales (Burham, 2005(Burham, , 2009Ollendick, 1983;Sandín, 1997;Scherer y Nakamura, 1968;Valiente, Sandín, Chorot y Tabar, 2003) y también, aunque en menor medida, las situaciones generadoras de ansiedad escolar (Méndez, García-Fernández y Olivares, 1996;Morris, Finkelstein y Fisher, 1976;Steinhausen, Müller y Winkler, 2008;Swartz, Reyns, Henson y Wilcox, 2011). Sin embargo, aún existen algunas lagunas en la investigación como, por ejemplo, analizar la relación de la ansiedad escolar con otras variables relevantes del contexto escolar así como también estudiar las diferencias que se producen en estas variables entre los grupos de baja y alta ansiedad escolar.…”
Section: Introductionunclassified